Neonatal spinal muscular atrophy with brain magnetic resonance imaging hypersignal: a case report - Jieda, Xiaolin; Yang, Chaoge; Wu, Yue; Zhang, Rong; Xu, Wanting; Dong, Wenbin (Frontiers in Pediatrics, 2025)
Spinal muscular atrophy (SMA) is an autosomal recessive genetic disorder marked by progressive, symmetrical muscle weakness and atrophy. While only a limited number of studies on human SMA have demonstrated brain involvement, there are also few reports detailing early brain MRI changes in SMA patients. In this paper, we present the case of a child whose initial symptom was limb hypotonia. The child's brain MRI revealed abnormal signal changes and genetic testing ultimately confirmed the diagnosis of SMA. By reviewing relevant literature, we aim to summarize the brain MRI signal changes observed in SMA patients and explore their possible mechanisms, with the goal of enhancing clinicians' ability to identify and treat neonatal SMA at an early stage.